Multilayer chemisorption-enabled MOF-based composite membrane for rapid and efficient trifluralin removal from wastewater - Sima Kazemi; Azadeh Tadjarodi; Abdolmajid Bayandori Moghaddam (Scientific Reports)
Abstract In this study, a composite membrane comprising NH2-MIL-101(Cr) and polyacrylonitrile was meticulously synthesized and electrospun to yield a seamlessly integrated structure, effectively targeting the removal of trifluralin, as a pollutant, from contaminated wastewater. The remarkable 95.08% removal efficiency achieved within a mere 15-min timeframe underscores the membrane’s exceptional adsorption capacity and rapid contaminant uptake. The interaction between trifluralin molecules and the membrane surface is facilitated by the intricate network of active sites provided by NH2-MIL-101(Cr), ensuring through pollutant capture. Furthermore, the synergistic interplay between NH2-MIL-101(Cr) and polyacrylonitrile not only enhances adsorption kinetics but also aligns with both Freundlich isotherm and pseudo-second-order kinetic models, elucidating the mechanism of multilayer chemisorption and confirming the membrane’s robust performance across various operating conditions. Notably, the membrane exhibits remarkable stability and sustained efficacy over multiple cycles, highlighting its potential for long-term and sustainable wastewater treatment solutions. This study underscores the critical role of composite membranes in efficiently mitigating water pollution challenges and emphasizes the promising prospects of NH2-MIL-101(Cr) and polyacrylonitrile composite membranes for widespread environmental remediation efforts.